2017
DOI: 10.4081/jlimnol.2017.1640
|View full text |Cite
|
Sign up to set email alerts
|

Fisheries impacts on lake ecosystem structure in the context of a changing climate and trophic state

Abstract: <p>Through cascading effects within lake food webs, commercial and recreational fisheries may indirectly affect the abundances of organisms at lower trophic levels, such as phytoplankton, even if they are not directly consumed. So far, interactive effects of fisheries, changing trophic state and climate upon lake ecosystems have been largely overlooked. Here we analyse case studies from five European lake basins of differing trophic states (Lake Võrtsjärv, two basins of Windermere, Lake Geneva and Lake M… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1
1

Relationship

4
3

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 70 publications
0
10
0
Order By: Relevance
“…Thus, shifts between phases of high and low water levels are behind many of the observed RSs in biotic time series in the early 1980s and the mid 1990s. Moreover, the measures of fisheries management that target the composition of fish communities, and the balance between predatory and non-predatory fish species, cascade down through the food web [64]. Such reorganization of fisheries management of the lake food webs took place in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, shifts between phases of high and low water levels are behind many of the observed RSs in biotic time series in the early 1980s and the mid 1990s. Moreover, the measures of fisheries management that target the composition of fish communities, and the balance between predatory and non-predatory fish species, cascade down through the food web [64]. Such reorganization of fisheries management of the lake food webs took place in the 1970s.…”
Section: Discussionmentioning
confidence: 99%
“…The unexpected trend in phytoplankton biomass observed in Lake Geneva is explained by a decrease in zooplankton grazing (Tadonleke et al, 2009), a change in phytoplankton taxonomic composition and an increase in phytoplankton biomass during winter and spring as a result of temperature increases during these seasons . Moreover, the abundance and taxonomic composition in zooplankton gradually changed with time because of decreases in food quality (Anneville et al, 2007 showed a shift from herbivorous to carnivorous copepods), changes in thermal conditions (Molinero et al, 2007) and trophic status (Molinero et al, 2006), and increased fish predation (Nõges et al, 2018).…”
Section: Temporal Dynamics Of Phytoplankton and Zooplankton In Lake Genevamentioning
confidence: 99%
“…For around 135 days per year, the lake is ice covered. As it is located in an area of flat relief the water outflow is restricted and the lake exhibits strong seasonal water level fluctuations with a maximal amplitude of 3.2 m during the snow melt (Cremona et al, 2018;Nõges et al, 2018). About half of the water in Lake Võrtsjärv comes from the river Väike-Emajõgi, which still possesses its natural flow regime (Cremona et al, 2017).…”
Section: Lake Võrtsjärvmentioning
confidence: 99%
“…About half of the water in Lake Võrtsjärv comes from the river Väike-Emajõgi, which still possesses its natural flow regime (Cremona et al, 2017). The main land use in the basin is agriculture, therefore extensive nutrient inputs since 1961 facilitate high phytoplankton biomass, to which cyanobacteria contribute 60% to 95% (Cremona et al, 2018;Nõges et al, 2018).…”
Section: Lake Võrtsjärvmentioning
confidence: 99%